The role of N-acetylcysteine in decreasing neutrophil-lymphocyte ratio in COVID-19 patients: A double-blind, randomized controlled trial - Prabowo, Nurhasan A.; Megantara, Marcellino A.; Apriningsih, Hendrastutik (Narra J, 2023)
N-acetylcysteine has antioxidant and anti-inflammatory activities that could potentially improve the clinical outcomes of coronavirus disease 2019 (COVID-19) patients. N-acetylcysteine potentially inhibits NLRP3 (NOD-, LRR- and pyrin domain-containing protein 3) inflammasome and results in control oxidative stress and cytokine release in COVID-19 patients. The aim of this study was to assess the effect of N-acetylcysteine in reducing the neutrophil-lymphocyte ratio (NLR) in COVID-19 patients. A randomized controlled clinical trial was conducted among severe and moderate COVID-19 patients. The treatment group received oral 1200 mg daily of N-acetylcysteine (three times a day) and the standard care for COVID-19, while the control group received standard care for COVID-19 and a placebo. The NLR was determined on the first day of admission and after the seventh day of treatment. A paired Student t-test was used to compare the NLR before and after treatment while independent Student t-test was used to compare the NLR between treatment and control groups. A total of 40 severe and moderate COVID-19 were enrolled, 20 people in each group, with a mean age was 44.68±13.24 years old. The mean NLR on the first day was 9.44 in the treatment group and 8.84 in the control group. After the seventh day, the mean NLR was 4.27 and 11.54 in the treatment group and control group, respectively. The mean changes of NLR (the pre-treatment compared to post-treatment) in the treatment and control group were reduced 4.05 and increased 3.34, respectively. The NLR in treatment group significantly decreased compared to the control group (p<0.001). In conclusion, N-acetylcysteine 1200 mg daily could reduce the NLR in severe and moderate COVID-19 patients.